Transition metal free regio-selective C–H hydroxylation of chromanones towards the synthesis of hydroxyl-chromanones using PhI(OAc)2 as the oxidant - Viswanadh, N. (Chemical Communications, 2018)
The chromanone scaffold is considered as a privileged structure in drug discovery. Herein, we report a highly efficient PhI(OAc)2 mediated regioselective, direct C–H hydroxylation of chromanones. This method offers easy access to substituted 6-hydroxy chromanones in moderate to good isolated yields, thus paving the way for their pharmaceutical studies.

Efficient synthesis of optically active neolignans ligraminol D and E - Ghotekar, Ganesh S.; Mujahid, M.; Muthukrishnan, M. (Synthesis-Stuttgart, 2019)
Efficient syntheses of optically active neolignans ligraminol D and E were achieved in four simple steps starting from easily available chiral benzyl glycidyl ethers. The products were obtained in good overall yields and high enantioselectivities. The protocol might also be useful in the synthesis of other ligraminols or related neolignans.
Keywords: benzyl glycidyl ether; Epoxide; lignan; ligraminol; Mitsunobu

New enantioselective synthesis of antiobesity drug lorcaserin - Ghotekar, Ganesh S.; More, Devidas A.; Nalla, Viswanadh; Muthukrishnan, M. (New Journal of Chemistry, 2019)
A simple and efficient enantioselective synthesis of anti-obesity drug lorcaerin starting from easily accessible 3-chlorostyrene oxide has been described for the first time employing hydrolytic kinetic resolution as a source of chirality. The protocol might also be useful in the synthesis of structural variants of lorcaserin.

Transition-metal-free benzannulation of tricarbonyl derivatives with arynes: access to 1,3-dinaphthol precursors for the synthesis of rhodamine dye analogues - Ghotekar, Ganesh S.; Shaikh, Aslam C.; Muthukrishnan, M. (Journal of Organic Chemistry, 2019)
Herein, we report a transition-metal-free annulation reaction of benzynes and 1,3-oxopentanedioate for the synthesis of highly functionalized naphthalene derivatives for the first time. Additionally, the representative naphthalene derivatives have been successfully transformed into the new series of rhodamine dye analogues.

1,6-Conjugate addition initiated formal [4+2] annulation of p-quinone methides with sulfonyl allenols: a unique access to spiro[5.5]undeca-1,4-dien-3-one scaffolds - Ghotekar, Ganesh S.; Shirsath, Sachin R.; Shaikh, Aslam C.; Muthukrishnan, M. (Chemical Communications, 2020)
An expedient one-pot synthesis of carbocyclic spiro[5.5]undeca-1,4-dien-3-ones via 1,6-conjugate addition initiated formal [4+2] annulation sequences by employing p-quinone methides and sulfonyl allenols is presented. Furthermore, this synthetic protocol tolerates a wide variety of p-quinone methides and sulfonyl allenols and affords the corresponding structurally unique spiro[5.5]undeca-1,4-dien-3-ones in good yield under mild reaction conditions.

Silver-catalyzed cascade cyclization/1,6-conjugate addition of homopropargyl sulfonamides to p-quinone methides: an approach to diverse 3-diarylmethine substituted dihydropyrroles - Shirsath, Sachin R.; Ghotekar, Ganesh S.; Bahadur, Vir; Gonnade, Rajesh G.; Muthukrishnan, M. (Journal of Organic Chemistry, 2020)
A silver-catalyzed cycloisomerization/1,6-conjugate addition of homopropargyl sulfonamides to p-quinone methides to access diverse diarylmethine substituted dihydropyrroles has been disclosed. The reaction pathway involves an intramolecular cascade cyclization of homopropargyl sulfonamides to generate a highly reactive dihydropyrrole intermediate in situ followed by conjugate addition with p-quinone methides. This method provides an efficient and scalable route for the synthesis of 3-diarylmethine substituted dihydropyrroles, in one pot.

BF3.Et2O-catalyzed selective C-4 alkylation of isoquinolin1(2H)-ones employing p-quinone methides - More, Devidas A.; Ghotekar, Ganesh S.; Muthukrishnan, M. (Chemistry-an Asian Journal, 2023)
The direct C-4 alkylation of isoquinolin-1(2H)-one moiety is a challenging transformation in organic synthesis. Here we present a practical and efficient synthesis of C-4 alkylated isoquinolin-1(2H)-ones through conjugate addition of isoquinolin-1(2H)-ones to p-quinone methides for the first time. The process is facilitated by Lewis acid catalysis and this operationally straightforward, mild, metal-free and one-pot transformation provides a wide range of C-4 alkylated isoquinolin-1(2H)ones at ambient temperature in good to excellent yields.

Palladium-catalyzed oxidative cyclization of ?-allenols in the presence of TBN: access to 3(2H)-furanones - Ghotekar, Ganesh S.; Shinde, Ravi A.; Saswade, Sagar S.; Muthukrishnan, M. (Journal of Organic Chemistry, 2023)
A new palladium-catalyzed oxidative cyclization of alpha-allenols is described. The readily accessible alpha-allenols participate in intra-molecular oxidative cyclization in the presence of TBN to grant access to multisubstituted 3(2H)-furanones, which are common motifs in several biologically important natural products and pharmaceuticals.
Keywords: Alternatively; conditions; cumbersome workup; intramolecular electrophilic; multiple reaction steps; noted examples

Manganese-mediated cascade radical oxidative cyclization/1,6-conjugate addition of unsaturated oximes with p-quinone methides: facile access to β,β-diarylmethine substituted isoxazolines - Vara, Vijay; Thete, Kishor R.; Ghotekar, Ganesh S.; Muthukrishnan, M. (Chemistry-An Asian Journal, 2025)
A simple and efficient strategy for the synthesis of structurally diverse beta,beta-diarylmethine substituted isoxazoline derivatives have been developed. This approach employs a manganese-promoted oxidative cyclization coupled with a 1,6-conjugate addition of unsaturated oximes to p-quinone methides. The key features of this study include the formation of C-O and C-C bonds through intramolecular and intermolecular interactions, facilitated by in situ generated iminoxyl radicals. beta,beta-diarylmethine substituted isoxazolines, bearing a wide range of functional groups, were isolated in high yields.
Keywords: p-Quinone methide; diarylmethine substituted isoxazolines; Iminoxy radical; Manganese catalyzed